Intravenous formulation of Panax notoginseng root extract: human pharmacokinetics of ginsenosides and potential for perpetrating drug interactions - Pintusophon Salisa; Niu Wei; Duan Xiao-na; Olaleye Olajide E; Huang Yu-hong; Wang Feng-qing; Li Yan-fen; Yang Jun-ling; Li Chuan (Acta Pharmacologica Sinica, 2019)
XueShuanTong, a lyophilized extract of Panax notoginseng roots (Sanqi) for intravenous administration, is extensively used as add-on therapy in the treatment of ischemic heart and cerebrovascular diseases and comprises therapeutically active ginsenosides. Potential for XueShuanTong–drug interactions was determined; the investigation focused on cytochrome P450 (CYP)3A induction and organic anion-transporting polypeptide (OATP)1B inhibition. Ginsenosides considerably bioavailable for drug interactions were identiﬁed by dosing XueShuanTong in human subjects and their interaction-related pharmacokinetics were determined. The CYP3A induction potential was determined by repeatedly dosing XueShuanTong for 15 days in human subjects and by treating cryopreserved human hepatocytes with circulating ginsenosides; midazolam served as a probe substrate. Joint inhibition of OATP1B by XueShuanTong ginsenosides was assessed in vitro, and the data were processed using the Chou–Talalay method. Samples were analyzed by liquid chromatography/mass spectrometry. Ginsenosides Rb1, Rd, and Rg1 and notoginsenoside R1 were the major circulating XueShuanTong compounds; their interaction-related pharmacokinetics comprised compound dose-dependent levels of systemic exposure and, for ginsenosides Rb1 and Rd, long terminal half-lives (32‒57 and 58‒307 h, respectively) and low unbound fractions in plasma (0.8%‒2.9% and 0.4%‒3.0%, respectively). Dosing XueShuanTong did not induce CYP3A. Based on the pharmacokinetics and inhibitory potency of the ginsenosides, XueShuanTong was predicted to have high potential for OATP1B3-mediated drug interactions (attributed chieﬂy to ginsenoside Rb1) suggesting the need for further model-based determination of the interaction potential for XueShuanTong and, if necessary, a clinical drug interaction study. Increased awareness of ginsenosides’ pharmacokinetics and XueShuanTong–drug interaction potential will help ensure the safe use of XueShuanTong and coadministered synthetic drugs.